Effectiveness of tooth brushing training for parents with special needs children - Rizkika, Nabila; Susanto, Henry Setyawan; Suhartono, Suhartono (Odonto : Dental Journal, 2023)
Background: Special needs children (SNC) have poor oral hygiene status than normal children. Tooth brushing is the most efficient mechanical method to improve dental hygiene in SNC. SNC has difficulties in performing tooth brushing due to their limitation, family support is needed to empower SNC to perform oral hygiene activities. The aim of this study is to asses the effectiveness of toothbrushing training in parents with SNC to decrease plaque index compare to parents who were not trained Method: This study used quasy experimental with non-equivalent control group design. The subjects of this study were 28 students with special needs at SLB Negeri Purwosari Kudus. Data analisys using paired samples t test. Result: The result showed that average plaque index of SNC before tooth brushing training in their parents was 3,297 and after the intervention the average plaque index decrease to 2,401. SNS plaque index decreased by 27% and statistically proven with p value <0,0001 (p <0,05). Conclusion: there is a significant influence of tooth brushing training in parents with SNC on the decreasing of SNC plaque index. Keyword: special needs children, tooth brushing training, plaque index